2019
DOI: 10.1111/vec.12874
|View full text |Cite
|
Sign up to set email alerts
|

Antivenin‐associated serum sickness in a dog

Abstract: Objective:To describe a case of documented serum sickness in a dog following administration of a single dose of a novel antivenin crotalidae polyvalent. Case Summary:A 4-year-old female neutered mixed breed dog developed recurrent signs of hypersensitivity (swelling, edema, urticaria/hives, gastrointestinal signs, vasculitis) at 1 and 2 weeks following administration of a single unit of a novel antivenin crotalidae polyvalent plasma product. Both episodes were treated with antihistamines and glucocorticoids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…There is a possibility that if venom from a different snake species had been used, then different outcomes might have occurred. Antivenom is composed of antibodies to various aspects of snake venom and can include whole immunoglobulin G or antigen‐binding fragments formed after pepsin digestion (F(ab’)2) 2,5–7,9,12,17,23,26,27 . The North American antivenom product contains both the fragment crystallizable region of antibody (Fc) and F(ab’)2 portions of the antibody structure 2,5–7,9,12,17,22,26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a possibility that if venom from a different snake species had been used, then different outcomes might have occurred. Antivenom is composed of antibodies to various aspects of snake venom and can include whole immunoglobulin G or antigen‐binding fragments formed after pepsin digestion (F(ab’)2) 2,5–7,9,12,17,23,26,27 . The North American antivenom product contains both the fragment crystallizable region of antibody (Fc) and F(ab’)2 portions of the antibody structure 2,5–7,9,12,17,22,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Antivenom is composed of antibodies to various aspects of snake venom and can include whole immunoglobulin G or antigen‐binding fragments formed after pepsin digestion (F(ab’)2) 2,5–7,9,12,17,23,26,27 . The North American antivenom product contains both the fragment crystallizable region of antibody (Fc) and F(ab’)2 portions of the antibody structure 2,5–7,9,12,17,22,26,27 . b Since the Fc portion of the antibody binds complement, it is considered to be the most immunogenic, which has been shown in other Fc‐containing antivenom products 5,9,27 .…”
Section: Discussionmentioning
confidence: 99%
“…14,24 However, when an animal is given a whole immunoglobulin product from a different species, antibodies can be found in that animal's bloodstream in 14 to 21 days. 9,21 This raises a question not explored in our study as to which product would be safest to use if a dog is given a fractionated or whole immunoglobulin antivenom product during its initial crotalid envenomation and then has another envenomation episode. We were unaware of any literature indicating a significantly higher reaction rate in dogs or people who have received antivenom on > 1 occasion.…”
Section: Discussionmentioning
confidence: 94%
“…However, the Fc portion also increases the risk of acute type I and delayed type III hypersensitivity reactions. [7][8][9] Two IgG products 10,11 are currently approved by the USDA for use in animals with crotalid envenomation (referred to subsequently as antivenoms C and D).…”
mentioning
confidence: 99%
“…38 The prevalence of serum sickness in dogs after administration of antivenom is unknown, but three case reports have been published reporting its occurrence after different antivenoms for viper envenomation in the United States. [41][42][43] In human medicine, there is no consensus regarding the diagnostic criteria for serum sickness; however, it is usually a clinical diagnosis. Australian authors have suggested that clinical signs, risk factors and laboratory data may contribute to a diagnosis.…”
Section: Discussionmentioning
confidence: 99%